Engagement model for NBC service units during chemical accidents - Inđić, Dejan R.; Luković, Zoran T.; Mučibabić, Spasoje D. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Chemical accidents are inevitable in modern technological development and they cause a number of effects on people, property and the environment. The nuclear-biological-chemical (NBC) services as well as specialized units of the Army of Serbia perform particular tasks in the elimination of the consequences of chemical accidents. This paper presents a modeling of the effects of chemical accidents and one possible method for the selection of NBC services engaged in the elimination of the consequences of chemical accidents, using the method of analytic hierarchy processes. Introduction Chemical accidents are inevitable in modern society, and the consequences that arise degrade the environment and hinder the work of man. In an integrated response to chemical accidents, different social structures are involved, among which the most significant are the units of the Army of Serbia. The paper presents a method of selecting a specialized Army unit (NBC service unit) that could be successfully engaged in eliminating the consequences of chemical accidents. Modeling the effects of chemical accidents In order to obtain valid data on the magnitude of consequences of chemical accidents, modeling has to be carried out through the Accident scenario. This paper presents a chemical accident in an urban environment during the transportation of hydrofluoric acid. Chemical accidents in transport are most common and account for 40% of all accidents. When a chemical accident occurs, it is necessary to determine the concentration of hazardous substances modeled as follows: LC50 - median lethal concentration; IDLH - concentration dangerous to human health and 0.1 IDLH - concentration dangerous for sensitive population (children, elderly and sick). After the completion of calculations, the ranges of dangerous fumes of hydrofluoric acid are determined to be from 310 to 360 m for IDLH and from 1700 to 1900 m for 0.1 IDLH. All this leads to the conclusion that in the response to chemical accidents, NBC service units must be included in order to participate in the elimination of consequences. AHP method In the field of multiple criteria decision-making, the most important is the method of analytic hierarchy process (AHP method). Proper defining of objectives, criteria and decision alternatives results in the initial parameters for solving a specific problem - a choice of NBC service units for the elimination of consequences of chemical accidents. Four application stages (problem structuring, data collection, evaluation and determination of the relative weights of decision problems) lead to the selection of the best or optimal alternative. Involvement of the NBC service in eliminating the effects of chemical accidents For a concrete example, the decision maker should select an appropriate NBC service unit for eliminating the consequences of chemical accidents by properly defining the decision making criteria based on the alternatives offered. The AHP method and Expert Choice software program help us arrive at an optimal solution, as shown in the synthesis table for the selection of the optimal alternative. The selected units for solving modeled chemical contamination accidents would carry out dedicated tasks (chemical reconnaissance and decontamination) in a period of about 2.5 hours, not including the time of arrival to the site of the accident (which can last for several hours), which is a major problem in their use due to their uneven distribution in the Republic of Serbia. Conclusion The precise implementation of the AHP method, led to the following ranking in the model: - unit for protection against nuclear and chemical accidents – ranked the first with 0.433 index points; - NBC service temporary staff - second in rank with 0.265 index points; - decontamination unit - ranks third with the 0.177 index points; - reconnaissance unit - fourth in rank with 0.125 points. It can be thus concluded that, for the purposes of engaging in the elimination of the consequences of chemical accidents, we should opt for the unit for protection against nuclear and chemical accidents as the optimal solution, followed by the backup version of the NBC service with temporary staff. Decontamination and reconnaissance units can be used independently during limited time and only for pre-defined tasks. If NBC service units are to be engaged in the future in dealing with similar problems, the method of their rapid "switch" from their peacetime locations to accident sites has to be developed.